Biosynthesis of supported Pd nanoparticles using poplar leaf as a reducing agent and carrier: A green route to highly efficient and reusable Suzuki coupling reaction catalyst. Issue 8 (3rd August 2017) - Liu, Guanghui; Bai, Xuefeng; Lv, Hongfei
ABSTRACT: A green process for the synthesis of supported Pd nanoparticles (NPs) using poplar leaf extract (PLE) as a reducing agent and the extracted residue of poplar leaf (RPL) as a carrier is reported. The Pd/RPL nanocomposites were characterized by XRD, TEM, SEM, EDS, XPS, FTIR, and ICP-AES. The spherical Pd NPs had a mean particle size of 3.1 nm and were evenly distributed on the RPL surface. More importantly, the Pd/RPL nanocomposites were used as a heterogeneous catalyst, which presented superior catalytic activity for the Suzuki coupling reaction. In addition, only a slight loss in the catalytic activity was observed after six recycles.